A BLOCKCHAIN BASED SECURE AND EFFICIENT VALIDATION SYSTEM FOR DIGITAL CERTIFICATES - C.RASHMI, G. ARCHANA, K. RASHMIKA, K. SPANDANA, CH. MANASA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Certificate forgery has been a persistent issue across various industries, causing concerns in education, professional certifications, and legal documentation. In the past, verifying certificates was a manual and time-consuming process, involving physical examination of paper-based documents and cross-referencing with centralized databases or authorities. Unfortunately, this approach lacked transparency, was slow, and provided opportunities for fraudulent activities. Moreover, the vulnerability of traditional paper certificates to tampering and counterfeiting raised doubts about their authenticity and reliability. Thankfully, recent technological advancements have opened up a promising solution to combat certificate forgery by utilizing blockchain technology for certificate verification. Therefore, this project proposes an innovative approach to tackle this problem head-on. By harnessing the capabilities of blockchain, this work aims to create a robust and tamper-resistant certificate verification platform. Blockchain technology offers a decentralized and immutable way of storing and managing data, making it an ideal candidate to revolutionize certificate verification. With this system, the entire process becomes more efficient and secure. Each certificate issuance is recorded in a tamper-proof manner, complete with a timestamp, which virtually eliminates the possibility of altering or deleting information. The decentralized nature of blockchain removes the need for reliance on a central authority, reducing the risk of data manipulation and fostering trust in the verification process. This means that certificates can be verified without the involvement of a single controlling entity, making the system more reliable and transparent. In addition, the proposed system addresses the challenges associated with certificate forgery and offers a secure, efficient, and trustworthy solution. By leveraging blockchain technology, this proposed system can revolutionize current practices and ensure that certificates hold their true value and authenticity, thus maintaining the integrity of various industries plagued by this long-standing problem.